The Pengaruh Pengembangan Karir terhadap Kinerja Karyawan melalui Motivasi pada Karyawan Politeknik Pelayaran Surabaya - Ahmad Alfajri Prasetya; Budiono (Universitas Negeri Surabaya, 2025)
This study examines the impact of career development on employee performance, with motivation serving as a mediating variable. The primary objective is to understand how career development programs implemented at Agency X Surabaya enhance employee motivation, which in turn contributes to improved performance. Data were collected through questionnaires distributed via Google Forms, as well as interviews with HR staff and observations of career development initiatives such as the Talent Pool and Training Needs Analysis, conducted both internally and externally. “Data analysis consists of descriptive analysis using the Three Box Method (Ferdinand, 2006), as well as inferential analysis using Structural Equation Modeling (SEM) with the help of SmartPLS 3.0 software.”. The implication of this study is that agencies need to improve and update clear career development programs and provide additional incentives or rewards for non-civil servant employees, so that it will have a positive impact on employee motivation, commitment, and performance, thus impacting organizational performance improvement. The findings indicate that career development has a significant positive effect on employee performance, with work motivation playing a crucial role in strengthening this relationship. Employees who have access to clear career advancement opportunities tend to be more motivated, leading to better performance outcomes. These results align with previous studies that highlight the essential role of work motivation in improving performance. However, the study also identifies an imbalance in the implementation of career development programs, particularly affecting non-permanent or contract employees who perceive limited opportunities for career progression.